2016
DOI: 10.1073/pnas.1604818113
|View full text |Cite
|
Sign up to set email alerts
|

Joint representation of translational and rotational components of optic flow in parietal cortex

Abstract: Terrestrial navigation naturally involves translations within the horizontal plane and eye rotations about a vertical (yaw) axis to track and fixate targets of interest. Neurons in the macaque ventral intraparietal (VIP) area are known to represent heading (the direction of selftranslation) from optic flow in a manner that is tolerant to rotational visual cues generated during pursuit eye movements. Previous studies have also reported that eye rotations modulate the response gain of heading tuning curves in VI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…Alternatively, other groups proposed retinal slip is separated from flow due to selfmotion by combining tuning shifts with gain modulation of neuronal responses (Beintema and van den Berg, 1998). Analysis of single-unit responses in VIP to flow patterns with different combinations of translational and rotational components revealed that some cells showed joint, inseparable tuning for specific combinations (Sunkara et al, 2016). These responses were similar to those seen in real pursuit, suggesting that VIP simultaneously represents both the distorted retinal flow pattern and the veridical heading, which could be extracted by a downstream area.…”
Section: Theoretical Retinal Mechanismsmentioning
confidence: 99%
“…Alternatively, other groups proposed retinal slip is separated from flow due to selfmotion by combining tuning shifts with gain modulation of neuronal responses (Beintema and van den Berg, 1998). Analysis of single-unit responses in VIP to flow patterns with different combinations of translational and rotational components revealed that some cells showed joint, inseparable tuning for specific combinations (Sunkara et al, 2016). These responses were similar to those seen in real pursuit, suggesting that VIP simultaneously represents both the distorted retinal flow pattern and the veridical heading, which could be extracted by a downstream area.…”
Section: Theoretical Retinal Mechanismsmentioning
confidence: 99%
“…For example, large-field angular visual motion heavily biases SVV and elicits abnormally large postural sway in patients with spinocerebellar ataxia type 6 (Bunn et al, 2015; Dakin et al, 2018). Neural representations of large-field angular visual motion, which may contribute to head orientation estimates, have been identified in multiple brain regions of monkeys, including the cerebellum (Kano et al, 1990, 1991), brainstem (Waespe and Henn, 1977), and ventral intraparietal area (Sunkara et al, 2016). The semi-circular canals (Fig.…”
Section: Visual Motion Cues Signal Changes In Head Tiltmentioning
confidence: 99%
“…48 Areas MT and MST also have reciprocal connections with ventral intraparietal area (VIP), a site that contributes to pursuit 49 and combines translational and rotational components of self-motion. 19 …”
Section: Neural Mechanisms Of Texture Pursuitmentioning
confidence: 99%
“…18 On the other hand, recent studies have shown coupling of translational and rotational components of optic flow stimuli in brain areas that are also involved with pursuit, such as ventral intraparietal area (VIP). 19 Here we propose that pursuit is a fully three-dimensional task that utilizes all three degrees of freedom of the eye's rotation, including torsion. We will refer to this as ''texture pursuit'' and refer to the classical experimental paradigm, utilizing stimuli without significant spatial extent (and hence without detectable rotation), as ''point pursuit.''…”
mentioning
confidence: 99%